Sustainability of an ideal term as exemplified by the Polish medical terminology at the turn of the 19th and 20th century - Jankowiak, Lucyna Agnieszka (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The analysis is based on the best 940 terms (ideal terms) from synonymic strings contained in Słownik terminologii lekarskiej polskiej (English: Polish Medical Terminology Dictionary) of 1881. The purpose of this analysis is to determine the sustainability of the ideal terms between 1881 and 1905 when the next medical dictionary was published. The ideal terms maintain their position at a rate of 67%, which shows that the choices of names made by physicians in the 2nd half of the 19th century were correct. At the same time, the sustainability of the ideal terms has been accompanied by negative processes: the synonymy is being insignificantly reduced on one hand while being even multiplied on the other hand.